1981
DOI: 10.1113/jphysiol.1981.sp013882
|View full text |Cite
|
Sign up to set email alerts
|

The effect of burst patterning of preganglionic input on the efficacy of transmission at the cat stellate ganglion

Abstract: SUMMARY1. The effect of burst patterned preganglionic stimulation on the efficacy of transmission at the cat stellate ganglion in vivo was studied to determine whether the increase in acetylcholine (ACh) release that occurs at preganglionic terminals with similar stimulation is synaptically active.2. Stimulation of the whole or a portion of the thoracic sympathetic trunk between rami T4 and T5 with recording of evoked compound action potentials in the inferior cardiac nerve yielded a preparation with a sublimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…First, despite the above limitations and options for complex recruitment patterns, Birks and colleagues (Birks 1978;Birks and Isacoff 1988;Birks et al 1981) reported a predictable change in amplitude of the postganglionic compound AP following graded stimulation of the preganglionic neurons. Furthermore, delicate studies by John Horn's group in the bullfrog provided evidence that the aorta vasoconstrictor response scaled to the preganglionic sympathetic stimulation, and this vasoconstriction was minimized by both inhibition of postganglionic neurotransmitter release (guanethidine) and reduction in ganglionic transmission through postjunctional antagonism with tubocurarine (Thorne and Horn 1997).…”
Section: The Validity and Reliability Of Postganglionic Sna To Reflecmentioning
confidence: 99%
“…First, despite the above limitations and options for complex recruitment patterns, Birks and colleagues (Birks 1978;Birks and Isacoff 1988;Birks et al 1981) reported a predictable change in amplitude of the postganglionic compound AP following graded stimulation of the preganglionic neurons. Furthermore, delicate studies by John Horn's group in the bullfrog provided evidence that the aorta vasoconstrictor response scaled to the preganglionic sympathetic stimulation, and this vasoconstriction was minimized by both inhibition of postganglionic neurotransmitter release (guanethidine) and reduction in ganglionic transmission through postjunctional antagonism with tubocurarine (Thorne and Horn 1997).…”
Section: The Validity and Reliability Of Postganglionic Sna To Reflecmentioning
confidence: 99%
“…Gain at the pre‐to‐postganglionic node in the vasoconstrictor pathway is known to occur, especially during bursts of activity (Birks et al . ; Birks & Isacoff, ). Sympathetic preganglionic neurones in the un‐anaesthetised ( in situ ) Wistar‐Kyoto rat fire at 2.5 Hz with an SD of 1.6 Hz (Briant et al .…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of the data from the method employed, by which additional preganglionic axons joining the sympathetic chain at each segment were stimulated, seems justified by studies of the electrophysiological properties of sympathetic ganglia. Larrabee and Bronk [ 10 ] and Birks et al [ 23 ] examined the electrophysiological properties of postganglionic neurones in the cat stellate ganglion and clearly showed that maximal stimulation of different populations of preganglionic axons in the sympathetic chain, evoked compound action potentials in different groups of postganglionic neurones in the inferior cardiac nerve. Therefore, in the present study it seems reasonable to conclude that the magnitude of the functional cardiac response reflected the number of preganglionic axons activated at each electrode position.…”
Section: Discussionmentioning
confidence: 99%